Legal Implications of Nominee Schemes in Foreign Ownership of Limited Liability Companies in Indonesia - Viola Audy; Amad Sudiro (Universitas Muhammadiyah Sumatera Utara, 2026)
The nominee scheme is a common practice in foreign investment in Indonesia, whereby an Indonesian citizen lends their name to formally hold shares on behalf of a foreign party in order to circumvent legal ownership restrictions. This practice raises legal concerns as it contradicts principles of transparency and legality enshrined in the national legal system. This article aims to examine the legal implications of nominee arrangements in foreign ownership of limited liability companies (Perseroan Terbatas) through a normative juridical approach. The discussion focuses on the validity of nominee agreements under Indonesian positive law and the legal consequences for both the foreign investors and the Indonesian nationals acting as nominees. The study finds that nominee schemes contravene the Investment Law, the Company Law, and the principle of beneficial ownership, rendering such agreements null and void by law, and denying legal protection to the parties involved.